Pengaruh Kompensasi Finansial dan Motivasi Kerja Terhadap Kinerja Karyawan Divisi Operasional pada PT. Anugerah Waterpark Bunder - Jessica Indriyani Nababan; Dian Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Competition in the tourism industry, particularly in the water recreation sector, demands that every company has human resources capable of providing optimal service. Employee performance is one of the main factors determining a company's success in maintaining service quality, increasing visitor satisfaction, and achieving organizational targets. This study aims to analyze the effect of financial compensation and work motivation on employee performance in the Operational Division of PT. Anugerah Waterpark Bunder. This study uses a quantitative approach with a survey method. The study population was all employees of the Operational Division of PT. Anugerah Waterpark Bunder, totaling 35 respondents. Data collection was carried out using a questionnaire with semantic differential. Data analysis used IBM SPSS Statistics through validity tests, reliability tests, multiple linear regression analysis, partial tests (t), simultaneous tests (F), and coefficient of determination (R²). The results show that financial compensation has a positive impact on employee performance. Work motivation also has a positive impact on employee performance. Simultaneously, financial compensation and work motivation significantly influence employee performance, with a coefficient of 35.2%. This finding indicates that the financial compensation system has a greater influence on employee performance than work motivation. Therefore, companies need to optimize policies and develop sustainable human resources.